GAMBARAN PENGETAHUAN DAN SIKAP WUS DALAM UPAYA PENCEGAHAN KANKER SERVIKS MELALUI TES IVA DI PUSKESMAS PUTRI AYU - Nurfitriani Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2019)
In Indonesia Cervical cancer is Cancer with the highest prevalence of about 0.8% or about 98,692 patients.Data from the health department Jambi city indicated that the women of childbearing age that positive cervical cancer on examination IVA at the public health center Putri Ayu Jambi city. This study aimed to determine the correlation of knowledge and attitude of women of childbearing age with cervical cancer prevention efforts. This is a quantitative research by using Cross Sectional design. This study was conducted on Aprils/d August  2018 with samples were 45 respondents, it used questionnaire, analyzed as univariate.The findings indicated that, 24 respondents (53,3%) have hightprevention efforts, 27 respondents (60%) have hight knowledge, and than  21 respondents (46,7%) have positive attitude.The higer the knowledge the better the prevention efforts, the attitude of a person does not affect the influence of prevention efforts, prevention efforts do not affect the attitude. It is expected that the public health center can provide information to childbearing age about prevention cervical cancer by health promotion or counseling and giving motivation to women of childbearing age to do the examination IVA or pap smear.